ASSESSMENT OF THE EUROPEAN GROUND MOTION SERVICE ORTHO PRODUCTS FOR LANDFILL SYSTEMATIC OBSERVATION - Negula, Iulia Dana; Moise, Cristian; Dediu, Florina; Gheorghe, Mihaela; Tudor, Georgeta; Sefercik, Umut Güneş (Univ Agronomic Sciences & Veterinary Medicine Bucharest - Usamv, 2023)
The European Ground Motion Service (EGMS) is a new, open and freely available addition to the pan-European component of the core Copernicus Land Management Service (CLMS). The service offers very accurate and consistent information regarding the ground motion velocity that might be correlated with a wide range of circumstances, such as landslides, subsidence, volcanic activity and many others. The products (i.e., basic, calibrated and ortho) delivered by EGMS were generated based on Sentinel-1 time-series acquired between 2016 and 2020, using advanced Differential Synthetic Aperture Radar Interferometry (A-DInSAR) techniques. The present study addresses the suitability of the EGMS ortho products for the monitoring of 15 solid waste landfills located across the territory of Romania. The vertical displacements extracted for each selected landfill were analysed and correlated with the available background information (e.g., exploitation duration, the quantity of waste disposal per year, etc.). The study proved that EGMS might be an important tool for waste management since it enables the continued monitoring of the landfill settlement process.
Keywords: Advanced Differential Synthetic Aperture Radar Interferometry (A-DInSAR); European Ground Motion Service (EGMS); landfill monitoring; landfill settlement; Sentinel-1